Design and Implementation of Arduino-Based Sterilization Robot - Khalaf, Omar Raad; Almukhtar, Aya A. (Control Systems and Optimization Letters, 2023)
In this paper, the primary objective is to design implement a low-cost mobile robot used for the sterilization and control of toxic and flammable gas leaks in the polluted areas. To implement the proposed robot, we employ a tank robot structure equipped with sensors/modules for detection, sterilization, and environmental analysis. The robot is outfitted with a camera to enhance its surveillance capabilities. For sterilization, we utilize ultraviolet rays emitted by a UV Lamp (220V Sterilizer 8W-T5 Tube) in infested areas. Special sensors are strategically placed to identify gases and viruses in the target locations. The sensors include MQ-2 for detecting gases like methane, butane, and smoke, MQ-9 for identifying carbon monoxide and flammable gases, and MQ-135 for continuous measurement of air purity. The UV rays can be remotely activated and deactivated through an infrared control system. Simultaneously, the sensor values (MQ-2, MQ-9, MQ-135) are consistently monitored and transmitted to a central authority responsible for remote surveillance. If any hazardous or toxic gases are detected, the system triggers an alarm, notifying relevant authorities to take prompt action. This integrated approach ensures the efficient sterilization of contaminated areas while actively monitoring and responding to potential gas leaks. The combination of sterilization technology, gas detection sensors, and remote monitoring enhances the safety and effectiveness of the entire system. In the future developments, many approaches can be used such as increasing the controlling area by using Wi-Fi or LoRa and using additional sensors for harmful gas detection.